Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3 - Page 489: 73



Work Step by Step

We will use the rule $\frac{a^{m}}{a^{n}}=a^{m-n}$ in the simplification of the expression: $\frac{48b^{\frac{1}{3}}}{12b^{\frac{3}{4}}}$ $=\frac{48}{12}\times\frac{b^{\frac{1}{3}}}{b^{\frac{3}{4}}}$ $=4\times b^{\frac{1}{3}-(\frac{3}{4})}$ $=4\times b^{\frac{1(4)-3(3)}{12}}$ $=4\times b^{\frac{4-9}{12}}$ $=4\times b^{\frac{-5}{12}}$ $=\frac{4}{b^{\frac{5}{12}}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.